A diary in the strict sense of the term - Malinowski, Bronislaw 1884-1942 (Stanford University Press, 1989)
Extracts from the diaries of the renowned anthropologist, written during stays on New Guinea, Mailu and the Trobriand Islands. Combining private reflections with detached scientific observation, this book is an intimate portrait of aboriginal Pacific cultures and the foreign scientist who studied them.